Epstein-Barr Virus and Neurological Diseases - Zhang, Nan; Zuo, Yuxin; Jiang, Liping; Peng, Yu; Huang, Xu; Zuo, Lielian (Frontiers in Molecular Biosciences, 2022)
Epstein-Barr virus (EBV), also known as human herpesvirus 4, is a double-stranded DNA virus that is ubiquitous in 90–95% of the population as a gamma herpesvirus. It exists in two main states, latent infection and lytic replication, each encoding viral proteins with different functions. Human B-lymphocytes and epithelial cells are EBV-susceptible host cells. EBV latently infects B cells and nasopharyngeal epithelial cells throughout life in most immunologically active individuals. EBV-infected cells, free viruses, their gene products, and abnormally elevated EBV titers are observed in the cerebrospinal fluid. Studies have shown that EBV can infect neurons directly or indirectly via infected B-lymphocytes, induce neuroinflammation and demyelination, promote the proliferation, degeneration, and necrosis of glial cells, promote proliferative disorders of B- and T-lymphocytes, and contribute to the occurrence and development of nervous system diseases, such as Alzheimer’s disease, Parkinson’s disease, multiple sclerosis, acute cerebellar ataxia, meningitis, acute disseminated encephalomyelitis, and brain tumors. However, the specific underlying molecular mechanisms are unclear. In this paper, we review the mechanisms underlying the role of EBV in the development of central nervous system diseases, which could bebeneficial in providing new research ideas and potential clinical therapeutic targets for neurological diseases.